Brain Tissue Oxygen Response as Indicator for Cerebral Lactate Levels in Aneurysmal Subarachnoid Hemorrhage Patients. Issue 2 (21st April 2022) - Hosmann, Arthur; Schnackenburg, Philipp; Rauscher, Steffen; Hopf, Andreas; Bohl, Isabelle; Engel, Adrian; Brugger, Jonas; Graf, Alexandra; Plöchl, Walter; Reinprecht, Andrea; Gruber, Andreas
Abstract : Background: Early detection of cerebral ischemia and metabolic crisis is crucial in critically ill subarachnoid hemorrhage (SAH) patients. Variable increases in brain tissue oxygen tension (PbtO2 ) are observed when the fraction of inspired oxygen (FiO2 ) is increased to 1.0. The aim of this prospective study was to evaluate whether a 3-minute hyperoxic challenge can identify patients at risk for cerebral ischemia detected by cerebral microdialysis. Methods: Twenty consecutive severe SAH patients undergoing continuous cerebral PbtO2 and microdialysis monitoring were included. FiO2 was increased to 1.0 for 3 minutes (the FiO2 challenge) twice a day and PbtO2 responses during the FiO2 challenges were related to cerebral microdialysis–measures, ie, lactate, the lactate-pyruvate ratio, and glycerol. Multivariable linear and logistic regression models were created for each outcome parameter. Results: After predefined exclusions, 274 of 400 FiO2 challenges were included in the analysis. Lower absolute increases in PbtO2 (∆PbtO2 ) during FiO2 challenges were significantly associated with higher cerebral lactate concentration ( P <0.001), and patients were at higher risk for ischemic lactate levels >4 mmol/L (odds ratio 0.947; P =0.04). Median (interquartile range) ∆PbtO2 was 7.1 (4.6 to 12.17) mm Hg when cerebral lactate was >4 mmol/L and 10.2 (15.76 to 14.24) mm Hg at normal lactate values (≤4 mmol/L). Median ∆PbtO2 was significantly lower during hypoxic than during hyperglycolytic lactate elevations (4.6 vs. 10.6 mm Hg, respectively; P <0.001). Lactate-pyruvate ratio and glycerol levels were mainly determined by baseline characteristics. Conclusions: A 3-minute FiO2 challenge is an easy to perform and feasible bedside diagnostic tool in SAH patients. The absolute increase in PbtO2 during the FiO2 challenge might be a useful surrogate marker to estimate cerebral lactate concentrations and might be used to identify patients at risk for impending ischemia.